Kajian Etnobotani Serat Centhini - Kurniasih Sukenti; Edy Guhardja; Y. Purwanto (The Ethnobiological Society of Indonesia, 2004)
A research on ethrlobotarrical aspect on Serat Cethim, a Javanese classical literature written in the early of nineteenth century, had been conducted. This research used interdiscipline approach includes social-cultural, botany, ecology, agriculture, and biodiversioo, tha tfinally JOrmed a holistic analysis of natural and human resources at that time. The result shows that (1) Serat Centhini is an important Javanese classical literature consists of multidiscipline aspects which is potential to be revealed, analysed and developed forward This book is a reflection of fife of traditional Javanese people that contents aspects of philosophy, religion, social, culture, education, prychobgy and environmental resources; (2) Javanese perception about living is that life is a vertical and horikontal relationship, with honour each other and solidarity as their way of life. Their environmental concepts contents some of conservation value to the environment; (3) traditional knowledges about management and use of plants appear people efforts in stringing vertical and hori.zontal communication in order to reach barn:or!), in their 0; (4) the use of plants of Javanese people based on Serat Centhini covered about 331 species consists of plants for food material (158 species), construction material (10 species), equipment material (46 species), coloration material (6 species), ritual material (84 species), medicinal plants (104 species), cosmetics material (170 *exits), firs-wood, and other utib'ties; (5) some of the plants using have been existing till this time, including the traditional norms. But it is still necessary to do some scientific study on some potential plants to prove their typical qualiDi. Traditional 1107111 which is stilt relevant to the future should be introduced and inherited to young generation so it could be applied as a cultural conservation eifori.